Method for delivery and display of substances on cell surface. - Abdul Rahim, Raha; Sankara Varma, Nadimpalli Ravi; Mohd Yusoff, Khatijah; Foo, Hooi Ling (2004)

(untitled)
The present invention relates to a method for delivery and display of hybrid proteins on the surface of a host cell preferably Gram-positive bacteria. The bacteria displaying surface epitopes are useful as recombinant vaccines, for delivery of active group to animal host, as diagnostic reagents and for other biological and pharmaceutical purposes.